The Science of the Soul in Colonial New England - Rivett, Sarah (Book collections on Project MUSE., 2011)
Rivett challenges notions of Puritan provincialism as antithetical to the Enlightenment and demonstrates that, instead, empiricism and natural philosophy combined with Puritanism to transform the scope of the religious activity in colonial New England from the 1630s to the Great Awakening of the 1740s.